2002
DOI: 10.1002/j.2161-1874.2002.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Among Offenders With Substance Abuse Problems: Overlooked and Underused?

Abstract: The author examined correlates of social support among 101 offenders in corrections-based treatment programs. Respondents perceived high levels of support despite numerous interpersonal problems. Social support was significantly associated with visits, letters, arrests, and days in treatment ( p < .05).The author describes strategies for implementing family-oriented interventions in corrections-based programs.In this study, I examine social support among male and female inmates in institutionbased substance ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Having a larger percentage of non-drinking friends in the network has been linked with better treatment outcomes (Zywiak, Longabaugh, & Wirtz, 2002) and, similarly, having more drinking friends has been associated with poorer outcomes (Mohr, Averna, Kenny, & Del Boca, 2001). Researchers also have highlighted the importance of social networks for offenders (Lemieux, 2002; Litt & Mallon, 2003). Owens and McCrady (2014) found that reductions in the proportions of heavy drug users in the social network mediated substance use from pre- to post-incarceration and that the first month was the most critical time for implementing changes in the social network after release from jail.…”
Section: Introductionmentioning
confidence: 99%
“…Having a larger percentage of non-drinking friends in the network has been linked with better treatment outcomes (Zywiak, Longabaugh, & Wirtz, 2002) and, similarly, having more drinking friends has been associated with poorer outcomes (Mohr, Averna, Kenny, & Del Boca, 2001). Researchers also have highlighted the importance of social networks for offenders (Lemieux, 2002; Litt & Mallon, 2003). Owens and McCrady (2014) found that reductions in the proportions of heavy drug users in the social network mediated substance use from pre- to post-incarceration and that the first month was the most critical time for implementing changes in the social network after release from jail.…”
Section: Introductionmentioning
confidence: 99%
“…Hunter, Robison, & Jason, 2012), and can serve as an important protective factor for persons with substance abuse problems. However, substance users are more likely to be alienated from their non-using social networks and report significant relational problems (Lemieux, 2002). Kuo and colleagues (2013) found family members to be both supportive and unsupportive.…”
Section: 0 Introductionmentioning
confidence: 99%
“…10,11 Other studies have found that unstable social networks, such as marriages or employment, were associated with drug relapses of parolees released from prison. 12-14 These findings provide evidence that social support plays a role in the lives of recently incarcerated offenders, and may suggest a beneficial area for intervention for this population.…”
Section: Introductionmentioning
confidence: 99%